2020
DOI: 10.1111/mmi.14504
|View full text |Cite
|
Sign up to set email alerts
|

DksA plays an essential role in regulating the virulence of Borrelia burgdorferi

Abstract: Borrelia burgdorferi, the etiological agent for Lyme disease, survives in nature through a complex enzootic life cycle involving Ixodes ticks and many mammalian hosts (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 59 publications
0
32
0
Order By: Relevance
“…al. performed concurrently with our own investigation showed DksA is required for the infection of mice following intradermal inoculation with B. burgdorferi (63). Consistent with the data shown in our study, the requirement of DksA for mammalian infection was linked with dysregulation of the Rrp2-RpoN-RpoS pathway.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…al. performed concurrently with our own investigation showed DksA is required for the infection of mice following intradermal inoculation with B. burgdorferi (63). Consistent with the data shown in our study, the requirement of DksA for mammalian infection was linked with dysregulation of the Rrp2-RpoN-RpoS pathway.…”
Section: Resultsmentioning
confidence: 75%
“…al. that showed DksA was required for the expression of RpoS-regulated genes and for infection of mice following intradermal inoculation, however, the seroconversion of mice infected with dksA-deficient B. burgdorferi were not reported in that study (63). Therefore, DksA appears to play a stronger role in controlling the expression of lipoproteins required for mammalian infection than (p)ppGpp.…”
Section: Activation Of the B Burgdorferi Stringent Response By Changmentioning
confidence: 70%
See 2 more Smart Citations
“…Rrp2, along with transcriptional activator BosR and repressor BadR, activates the RpoN-RpoS (σ 54 -σ S ) sigma cascade, which in turn controls the production of OspC and several virulence factors [ 14 28 ]. Several additional regulators have been identified that differentially regulate gene expression during the tick-mammal transmission including DsrA [ 29 ], Hfq [ 30 ], Hbb [ 31 , 32 ], CsrA [ 33 35 ], BpuR [ 36 ], EbfC [ 37 ], BpaB [ 38 ], SpoVG [ 39 ], BBD18 [ 40 ], LptA [ 41 ], BadP [ 42 ] and DksA [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%